2004
DOI: 10.1001/archsurg.139.12.1309
|View full text |Cite
|
Sign up to set email alerts
|

Nasojejunal Tube Placement After Total Gastrectomy

Abstract: Hypothesis: Anastomotic disruption of the Roux-en-Y esophagojejunostomy after total gastrectomy is an infrequent complication that may lead to severe morbidity and mortality. Consequently, a nasojejunal tube (NJT) is frequently placed when this operation is performed. However, no studies have compared routine vs no placement of an NJT in patients undergoing total gastrectomy for gastric cancer, to our knowledge. Design: Randomized controlled trial to assess the need for routine nasojejunal decompression after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 13 publications
(14 reference statements)
2
13
1
Order By: Relevance
“…Not surprisingly, and consistent with published data, surgical site infection and sepsis are the two most common metrics of NSQIP measured morbidity in this study (16). The organ space SSI of 7.05% is consistent with published rates of anastomotic leaks in recent literature ranging from 5 to 7%, however without targeted NSQIP data collection, the exact proportion of anastomotic leaks rather than other surgically-related causes of intra-abdominal infection cannot be defined precisely (1720). …”
Section: Discussionsupporting
confidence: 83%
“…Not surprisingly, and consistent with published data, surgical site infection and sepsis are the two most common metrics of NSQIP measured morbidity in this study (16). The organ space SSI of 7.05% is consistent with published rates of anastomotic leaks in recent literature ranging from 5 to 7%, however without targeted NSQIP data collection, the exact proportion of anastomotic leaks rather than other surgically-related causes of intra-abdominal infection cannot be defined precisely (1720). …”
Section: Discussionsupporting
confidence: 83%
“…Nasogastric intubation has been thought to reduce postoperative respiratory complications and the incidence of anastomotic leaks after gastrointestinal surgery. However, the necessity of nasogastric decompression following radical gastrectomy has been increasingly queried over the last decade [10,11,12,13,14]. …”
Section: Discussionmentioning
confidence: 99%
“…However, their trial neither aimed to address this issue, nor was it adequately powered to allow for any definitive conclusions. A recent prospective, randomised and adequately powered trial has shown the NJ tube to be unnecessary in elective total gastrectomies [15]. While the lack of uniformity remains the main finding in the present study, there was a tendency in Norway and Sweden to remove the tubes more liberally.…”
Section: Discussionmentioning
confidence: 63%